A global examination of country-level factors impacting corruption. (7th September 2021) - Merhi, Mohammad I.; Ahluwalia, Punit
Corruption is a widely discussed phenomenon in news media, public policy debates, among social activists and within governments. In recent years, it has been suggested that greater use of digital technologies can lower corruption. This paper attempts to explore this question and find out some of the relevant relationships between macro-level factors and country level levels of corruption. Secondary data published by the United Nations, Transparency International, and other similar organisations is used to analyse and confirm the proposed relationships. The results show that telecommunication, freedom of press, and e-participation are critical antecedents to corruption. The paper also examines indirect relationships between macro level actors and corruption. The results and their implications are discussed for research and practitioners.